Overall buckling behaviour of stainless-clad bimetallic steel welded circular section columns - Ban, Huiyong; Zeng, Zhuo; Zhao, Pingyu (Structures (Oxford), 2025)
Stainless-clad (SC) bimetallic steel is a high-performance laminated steel with excellent corrosion resistance and acceptable cost. The overall buckling behaviour and design of SC bimetallic steel welded circular section columns are addressed in this paper through experimental and finite element (FE) analyses. A total of four specimens were manufactured and subject to axial compression tests, and the initial geometric imperfections as well as the residual stress were measured. The buckling deformation, load versus displacement responses and strain development of the tested specimens were further analysed. A three-dimensional FE model was established and validated against the test results. Subsequently, parametric analyses were conducted to analyse the overall buckling behaviour of such columns, and four parameters were involved herein, including the initial geometric imperfections, the residual stress, the clad ratio, and the material combination. Finally, the applicability of existing design methods is examined herein based on the FE results of 1512 columns. A new design method was proposed by adapting the Perry-Robertson formula derived for SC bimetallic steel, and a simplified design method adapted from European standard EN 1993–1–1 was also proposed with enhanced accuracy in predictions, which can be used for future research and engineering applications.